AB1036 Updated Results from The Pro Assessment of Inflammatory Arthritis Patients' Experience with IV Administered Biologic Therapy. (15th July 2016) - Gaylis, N.; Sagliani, J.; Black, S.; Tang, K.; Dehoratius, R.; Parenti, D.
Abstract : Background: Pt-reported outcomes (PRO) are used to assess pt-related benefit in clinical trials. Inflammatory arthritis (IA) pts are equally receptive to intravenous (IV) or subcutaneous (SC) biologic treatment 1 . Objectives: We obtained PRO data to understand characteristics of pts who receive IV biologic agents for IA. Methods: This was a questionnaire-based study conducted at a rheumatology practice with extensive clinical trial experience. A total of 100 pts enrolled & are included in this final analysis. Inclusion criteria: a diagnosis of IA with IV biologic use for ≥3 mo; ≥18 yrs age; able to read, write & speak English, willing to complete the questionnaire & a signed informed consent form. IV biologic treatment was per clinical practice; there were no treatment assignments & study drug was not supplied. The questionnaire had 30 questions which pts completed prior to receiving a regularly scheduled dose of IV biologic. Results: Mean (±SD) age of pts was 58.35 (±14.64) yrs with mean disease duration of 10.1 (±8.13) yrs (range 0.7–45 years). Pts were Caucasian (38%), African American (28%), Latino/Hispanic (22%), Asian/Pacific Islander (1%) & 11% not identified. IV biologics used were infliximab [IFX](71%), rituximab [RTX](12%), tocilizumab [TCZ](10%), abatacept [ABT](6%) & golimumab [GLM](1%). The mean duration of current IV therapy was 4.07 (±3.27) yrs (range 0.1 to 16.0 yrs). Pts' favorability perception of IV therapy BEFORE & AFTER starting IV therapy is shown in the Figure . Amongst all pts, "Extremely favorable" increased (p<0.05) from 33% to 71% after receiving IV therapy; the increase in "Extremely favorable" was evident in pts with or without previous SC biologic therapy. Of the 33% of pts reporting an "Extremely favorable" rating BEFORE starting IV therapy, 6% changed their opinion to a lesser rating AFTER starting therapy, whereas 44% of patients reporting "Extremely favorable" AFTER starting IV therapy had indicated a lesser rating BEFORE starting IV therapy. Conclusions: These results suggest that among IA pts receiving IV biologic therapy for treatment of IA, there is a high degree of pt satisfaction, including a similar favorability perception of IV therapy among pts who switched from a SC to an IV biologic. Our results support the concept that when there is a shared decision making discussion with pts regarding biologic treatments, the option of IV therapy should be an essential part of that discussion & that the IA pts' perspective should be given meaningful consideration. References: Bolge SC et al Arthritis Rheum 2013;65 Suppl 10:1023 Disclosure of Interest: N. Gaylis Grant/research support from: Janssen Scientific Affairs, LLC, J. Sagliani Grant/research support from: Janssen Scientific Affairs, LLC, S. Black Employee of: Janssen R & D, LLC, K. Tang Employee of: Janssen R & D, LLC, R. Dehoratius Employee of: Janssen Scientific Affairs, LLC, D. Parenti Employee of: Janssen Scientific Affairs, LLC